The Influence Of Work-Life Balance And Burnout On Job Satisfaction - Zahara Tussoleha RONY; Yulisyahyanti YULISYAHYANTI (International Journal of Environmental, Sustainability, and Social Science, 2022)
In the current era of globalization, the development of technology is so rapid, and the competition is so tight, it requires every individual to be able to improve his abilities and skills in order to improve his quality in the face of competition. The research was conducted to find out whether there is an effect of Work-Life Balance and Burnout on job satisfaction of facilities and infrastructure maintenance officers in the XYZ area. Data were obtained from 77 respondents from the entire population using primary data obtained through questionnaires. Data analysis is using descriptive statistics, instrument test, classical assumption test, multiple linear regression and hypothesis testing using the IBM SPSS Statistics 24 Program. facilities and infrastructure in the XYZ area. This shows that the work-life balance felt by the employees who maintain the facilities and infrastructure of the XYZ area will be able to improve job satisfaction well and can increase work productivity; Partially, the burnout variable has a negative but not significant effect on the job satisfaction. This shows that the decreasing burnout experienced by employees who maintain facilities and infrastructure in the XYZ area will be able to increase job satisfaction well, and can increase work productivity.